Kajian Kebutuhan Ventilasi Alami Ruangan pada Bangunan Gedung - Mia Wimala; Kennardy Winardo (Rekayasa Sipil, 2023)
The Indonesian National Standard (SNI) 6572:2001 on natural ventilation in buildings has not been updated in the last 20 years, while similar standards in other countries have been periodically improved. The development of science and technology, environmental conditions, coupled with the COVID-19 pandemic that affects the entire world are the basis for consideration of the adjustment of related standards. The purpose of this study is to look at the standards for natural ventilation in several countries, namely the United States, Singapore, Malaysia, and Australia, as well as identify criteria that can be applied according to conditions in Indonesia. The results showed that the need for natural ventilation in buildings in Indonesia by 5% has met the existing conditions. However, further studies regarding the need for natural ventilation that are adjusted based on the function of the room as determined by ASHRAE 62.1 need to be carried out.